2021
DOI: 10.9734/jalsi/2021/v24i1030265
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts of Sand Mining in Some Coastal Communities in Port Harcourt Metropolis Nigeria

Abstract: Sand mining activity is one of the serious environmental problems, as the rivers are widely exploited for river bed materials like sand resulting in land and river bed degradation as well as loss of riparian habitat. The aim of this research was to assess the environmental impacts of sand mining activities in some coastal communities of Port Harcourt metropolis. Three communities namely Choba, Abuloma and Chokocho were selected for the study because of good access to waterfront and regular outcry by communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Sand mining is one of such human activities, and if it is carried out uncontrolled, can result into negative consequences for the natural environment. Sand mining is the scooping of sand from portions of the earth surface for construction and other developmental purposes (Ohaeri et al, 2021). Studies have shown that the negative environmental effects of unguided and small-scale sand mining in most developing countries far outweigh the socio-economic benefits (Narh, 2016;Baba, 2017;Mohammed, 2017;Ohaeri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sand mining is one of such human activities, and if it is carried out uncontrolled, can result into negative consequences for the natural environment. Sand mining is the scooping of sand from portions of the earth surface for construction and other developmental purposes (Ohaeri et al, 2021). Studies have shown that the negative environmental effects of unguided and small-scale sand mining in most developing countries far outweigh the socio-economic benefits (Narh, 2016;Baba, 2017;Mohammed, 2017;Ohaeri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sand mining is the scooping of sand from portions of the earth surface for construction and other developmental purposes (Ohaeri et al, 2021). Studies have shown that the negative environmental effects of unguided and small-scale sand mining in most developing countries far outweigh the socio-economic benefits (Narh, 2016;Baba, 2017;Mohammed, 2017;Ohaeri et al, 2021). Some of the reported negative effects of unguided sand mining include environmental degradation, water pollution, soil structure destruction, soil erosion facilitation with abandoned pits acting as breeding grounds for water-related diseases and deathtraps (Jonah et al, 2015;Narh, 2016;Baba, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This upsets the balance of coastal ecosystems and makes them more likely to be washed away. In spite of the economic importance of sand mining, the practise of it can speed up erosion by making sediments along coastlines less stable [13]. Geophysical methods refer to scientific techniques used to study the Earth's subsurface and physical properties [14,15].…”
Section: Literature Reviewmentioning
confidence: 99%